ҚАРАҚАЛПАҚ ЭПОСЛАРЫНЫҢ СЫРТ ЕЛЛЕРДЕ ҮЙРЕНИЛИЎИНИҢ ТИЙКАРҒЫ ИЛИМИЙ АСПЕКТЛЕРИ АНАЛИЗИ - Алламбергенова, Г.К. (FAN va JAMIYAT, 2022)
The article provides a detailed analysis of the main scientific aspects of the Karakalpak epics studied by foreign scholars on the example of the epic "Edige". Also, the role of these comparative-typological studies in the history of study of Karakalpak epics abroad will be determined on the basis of reliable scientific and theoretical facts.